Rethinking Vocational Education in the Philippines: Does It Really Lead to Higher Wages? - Olfindo, Rosechin (Archīum Ateneo, 2018)
Vocational education is often seen as a means of enhancing the earning potential of disadvantaged workers — those with lower levels of general formal education, or without adequate skills to integrate into the labour market. International evidence on the effects of vocational education on earnings is mixed. An earlier study on the Philippines indicated that this type of education can increase the wages of low-educated workers. However, by using a more recent household survey and employing alternative statistical techniques, this paper finds contrasting evidence. The new estimates indicate that workers who obtained vocational education do not earn significantly more than those who did not. The differences in estimates imply that the wage effects of vocational education among Filipino workers remain unclear. Therefore, caution must be exercised while making policies that aim to promote vocational education as an alternative to general formal education.